Children and the internet: the new sociology of childhood and the use of visual methods - Ordosgoitia, Rocío López (2014)
For new generations, digital culture is mainly represented in the use of the Internet. Exploring the perception that children have in terms of their Internet skills presents challenges at methodological and conceptual levels. This article develops two approaches of the study of children uses of Internet: the new sociology of childhood and the use of visual methods when researching with children. It proposes to consider the relevance of these two elements in the process of approaching the diversity of experiences of children in their everyday interaction with Internet.